Dynamic Epistemic Logic I: Modeling Knowledge and Belief. Issue 9 (12th September 2013) - Pacuit, Eric
Abstract: Dynamic epistemic logic, broadly conceived, is the study of logics of information change . This is the first paper in a two‐part series introducing this research area. In this paper, I introduce the basic logical systems for reasoning about the knowledge and beliefs of a group of agents.